Contributions to the history of ocular toxoplasmosis in Southern Brazil - Melamed Cattan, Jacobo (2009)
The evolution of knowledge regarding ocular toxoplasmosis over the last 30 years is described based on studies and observations performed in Southern Brazil. The isolation of Toxoplasma gondii established the definitive diagnosis of the disease. It was proven that in most cases, the disease was acquired after birth, a concept supported by the description of numerous familial cases and observation of the disease many years after primary infection. Epidemiological studies showed important regional variations in the prevalence of the disease due to different factors, including the types of strains involved, of which type I predominates. The large number of patients also enabled detailed study of the different forms of clinical presentation of the disease and its complications. New parameters have been established for the use of steroids and the management of pregnant women with active lesions. Studies on the epidemiology of toxoplasmic infection in pregnant women and newborns showed a high prevalence of infection. The different factors of exposure to infection have also been studied. Gradually, preventive actions have been developed in the sphere of public health, although they have not been sufficiently effective. Trends for future research over the next few years are also outlined.